Differences in Levels of Depression in Elderly Who Take Curse and Do Not Take Curse in Ingin Jaya District, Aceh Besar - Eridha Putra; Mahruri Saputra; Martunis Martunis (Jurnal Smart Keperawatan, 2022)
The elderly are old people who already have a lot of time to practice their religious activities, including taking part in recitations. The elderly who do not regularly participate in recitation activities experience depressive symptoms such as; a lack of confidence, feeling lonely, and loss of enthusiasm and hope in life. This study aims to determine the difference in the level of depression in the elderly who attend recitations and do not attend recitations at Kaye Lee Village, Ingin Jaya District, and Aceh Besar District. This research is quantitative with a comparative descriptive approach. The number of respondents in this study was 88 seniors, with the condition 44 elderly people attended the recitation and 44 did not attend the recitation. Sampling was carried out using purposive sampling. The results showed that results of the Mann-Whitney test showed that the mean rank level of depression in the elderly in the group taking part in recitation was 38.52 and in the group not attending recitation was 50.49 and the p-value was 0.025. The level of depression in the group attending the recitation was lower than the group who did not attend the recitation, meaning that the elderly who were active in recitation activities had a lower risk of experiencing depression. It is recommended that the results of this study form the basis for establishing programs to empower the elderly in the community, such as recitation programs in the village for social interaction and spiritual needs with the surrounding community, especially on aspects of the quality of life for the elderly in facing old age.Keywords: depression; elderly; recitationPerbedaan Tingkat Depresi pada Lansia yang Mengikuti Pengajian dan Tidak Mengikuti Pengajian di Kecamatan Ingin Jaya Kabupaten Aceh BesarABSTRAK Lansia merupakan usia lanjut yang sudah memiliki banyak waktuuntuk mengamalkan kegiatan keagamaannya termasuk mengikuti pengajian. Lansia yang tidak mengikuti kegiatan pengajian secara rutin mengalami gejala-gejala depresi seperti merasa kesepian, kurang percaya diri, kehilangan semangat dan harapan. Penelitian ini bertujuan mengetahui perbedaan tingkat depresi pada lansia yang mengikuti pengajian dan tidak mengikuti pengajian di Desa Kaye Lee Kecamatan Ingin Jaya Kabupaten Aceh Besar. Penelitian ini bersifat kuantitatif dengan pendekatan deskriptif comparative. Jumlah responden dalam penelitian inisebanyak 88 orang lansia, dengan ketentuan lansia yang mengikuti pengajian 44 orang dan tidak mengikuti pengajian 44 orang. Pengambilan sampel dilakukan dengan menggunakan purposive sampling. Hasil penelitian menunjukkan dari hasil  uji  Mann-whitney  didapatkan  nilai  mean  rank  tingkat depresi lansia pada kelompok megikuti pengajian  sebesar  38,52  dan  pada  kelompok  tidak mengikuti pengajian 50,49 serta nilai p-value  0,025. Tingkat depresi pada kelompok mengikuti pengajian lebih rendah dibandingkan kelompok yang tidak mengikuti pengajian, artinya lansia yang aktif dalam kegiatan pengajian memiliki resiko lebih rendah dalam mengalami depresi. Disarankan hasil penelitian ini menjadi dasar penetapan program-program pemberdayaan lansia dalam masyarakat, seperti program pengajian di desa untuk interaksi sosial dan kebutuhan spiritual dengan masyarakat sekitar, terutama pada aspek kulitas hidup lansia dalam menghadapi masa tua.Kata Kunci: depresi; lansia; pengajian